Japan : Economic and Policy Developments. (IMF Staff Country Reports; Country Report ;, 2001)
The Japanese economy is vulnerable to external and domestic shocks. The new government has made a commitment to turn the fiscal situation around. The new policy framework provides the Bank of Japan with the scope to ease the policy stance. A deteriorating macroeconomic environment has exposed underlying structural problems in the banking sector. Over the past year, Japan maintained its traditional emphasis on pursuing further trade liberalization through the World Trade Organization (WTO) framework, while at the same time initiating talks on bilateral free trade agreements.